Wpływ soborowej zachęty do ekumenizmu i kontaktów międzyreligijnych na rozumienie dialogu - KAMYKOWSKI, Łukasz (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
The usage of the term «dialogue» in the language of the Church was inspired mostly by the philosophy of dialogue and international relations. However, a nearer context is given in Paul VI’s encyclical Ecclesiam suam, written between the second and third sessions of the Second Vatican Council. Dialogue is shown there as the way of the Church’s relation towards the world. The encyclical models the Church’s relationship to the world on doctor-patient relation. The dialogue model of doctor-patient relation is also present in the Council’s Constitution Gaudium et spes, however, the Council’s vision of the world seems more complex than the one of Ecclesiam suam. The Constitution distinguishes between various theological aspects of the world (Creation, sin, Salvation). Therefore, the world and the Church are no longer disjunctive, but they interpenetrate, especially when taking the more personal perspective of dialogue people have with people, which calls for another model of dialogue, at least complementary to the previous one. It may be found especially in points 22-24, which had not been fully recognized before John Paul II drew on them in many of his teachings. They demonstrate a Christological perspective on man, fraternal relations between all people as children of one God and a dialogue model of exchange of gifts as well as unity founded on the Trinity. Having said that, the Council’s perspective of dialogue has been perceived mostly through its documents on ecumenism (Unitatis Redintegratio) and relation to other religions (Nostra Aetate). They shed light on both dialogue models and the role of dialogue participants as representatives of communities. The latter calls for dialogue inside the communities, i.e. also in the Catholic Church herself. Summarized by Agnieszka Piskozub-Piwosz